Answer + Step-by-step explanation:
For each part of the question, fill in the given x (-5 and then x+9 and then -x) into the x^2 + 4x + 6 and do the squaring and times by 4 and add 6. This is three separate problems.
f(-5) means let x be -5.
(-5)^2 +4(-5) + 6
=25+ -20+6
=5+6
=11
f(-5) = 11
_______________
f(x+9) means let x be x+9. Just fill in x+9 in place of x and do the squaring and times by 4 and add 6.
(x+9)^2 + 4(x+9) + 6
=x^2 + 18x + 81 + 4x + 36 + 6
= x^2 +22x + 123
f(x+9) = x^2 + 22x + 123
__________________
f(-x) means let x be -x . Put -x in place of x and square it and times by 4 and add 6.
f(-x) = (-x)^2 + 4(-x) + 6
f(-x) = x^2 - 4x + 6